Cellulolytic and hemicellulolytic bacteria from the gut of Oryctes rhinoceros larvae - SITI LUSI ARUM SARI; ARTINI PANGASTUTI; ARI SUSILOWATI; TJAHJADI PURWOKO; EDWI MAHAJOENO; WAHYU HIDAYAT; IKOW MARDHENA; DEWI KURNIAWATI; ROBIAH ANITASARI (Society for Indonesian Biodiversity, 2016)
Sari SLA, Pangastuti A, Susilowati A, Purwoko Tj, Mahajoeno E, Hidayat W, Mardhena I, Panuntun DF, Kurniawati D, Anitasari R. 2016. Cellulolytic and hemicellulolytic bacteria from the gut of Oryctes rhinoceros larvae. Biodiversitas 17: 78-83. Lignocellulose is very potential as raw material for biofuel production because it is cheap, abundant and renewable. The main carbohydrate constituents of lignocellulosic material are cellulose and hemicelluloses rd instars were used in this research. The research succeeded to isolate 11 bacterial isolates from the gut of O. rhinoceros larvae. The screening result demonstrated that bacterial isolates had cellulolytic (72.7% of total isolates), and mannanolytic (100% of total isolates) activity. Based on the 16S rDNA sequence, 10 isolates were classified into Bacillus and only 1 isolate was classified into Citrobacter. The GOR2 which was closely related to Bacillus pumilus vit bac1 has the highest cellulolytic and xylanolytic activities. The isolate with the highest mannanolytic activity was the GOR7 which was closely related to Bacillus aryabhattai strain IHB B 6821.